Ceratophyllus (Monopsyllus) carniolicus, new flea species from the family Ceratophyllidae (Siphonaptera) - Brelih, Savo (Acta entomologica slovenica (Ljubljana), 2001)
We describe a new species of flea from the subgenus Monopsyllus found in the nest of Glis glis in Mt. Snežnik (Slovenia). Ceratophyllus (Monopsyllus) carniolicus sp. n. is a very rare species whose ecology and major host are as yet unknown.
Keywords: bolhe; polhi; zajedalci